Pneumococcal Surface Protein A: A Promising Candidate for the Next Generation of Pneumococcal Vaccines - Alghamdi, Saad; Sahibzada, Muhammad Umar Khayam; Shesha, Nashwa T.; Aslam, Akhmed; Kabrah, Ahmed; Atwah, Banan; Khidir, Elshiekh B.; Alsafi, Radi; Farash, Shouq Z; Mazhar, Abdulbari A.; Kiran, Myle Akshay; Alenzi, Faris Q. (Cellular and Molecular Biology, 2022)
Streptococcus pneumoniae is the bacterium that causes pneumococcal disease which often results in pneumonia, meningitis, otitis media, septicemia and sinusitis. Pneumonia, particularly, is a significant cause of worldwide morbidity and a global health burden as well. Treatment often relies on antimicrobials, to which the pathogen is frequently mutating and rendering infective. Consequently, vaccination is the most effective approach in dealing with pneumococcal antimicrobial resistance (AMR). Unfortunately, the current pneumococcal polysaccharide and conjugate vaccines have a narrow serotype coverage. Therefore, the current need for vaccines with a broader serotype coverage cannot be overstated. Pneumococcal Surface Protein A and C are potential vaccine candidate antigens present in over 90% of the strains from clinical isolates as well as laboratory non-encapsulated strains. Pneumococcal Surface Protein A is an active virulent factor that pneumococci use to evade complement-mediated host immune responses and has been shown to elicit immune responses against pneumococcal infections. This review explores the potential utilization of Pneumococcal Surface Protein A to immunize against S. pneumoniae.